Foamable silicone composition
Patent Information
- Application Number
- JP2022581596
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-07-02
Smart Images

Figure 0007631383000001 
Figure 0007631383000002 
Figure 0007631383000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to foamable silicone compositions. [Background technology]
[0002] As the power source for electric vehicles, a stable, safe and reliable battery pack is important for the quality of the vehicle, so the requirements for the hardness, elasticity, mechanical properties and other performance of the sealing material for the battery pack case are higher.
[0003] Foamable silicone materials, especially auto-dispensing type foamable silicone compositions that are dispensed via an automatic dispenser and cured into a foam at room temperature or high temperature, and then compressed to achieve sealing, are a new trend in solutions for sealing battery pack cases. If the hardness of the silicone foam is too high, it will be difficult to compress, and the upper cover of the battery pack will be easily deformed, leading to poor sealing. If the elasticity of the foam is too low, the resilience when pressurized will be insufficient, and leakage due to deformation or displacement of the battery pack will easily occur. Therefore, the resilience and hardness of the silicone foam are very important to ensure the safety of the sealing of the battery pack case.
[0004] CN1182187C has a density of 0.29~0.35g / cm 3 It has been disclosed that the elasticity of the foam can be improved by adding an organic sulfur compound such as 3-mercaptopropyltrimethoxysilane. However, the compression set (CS) (50%, 24h, 100°C) of the foam is still more than 20%, which is not conducive to good sealing performance. The mechanical properties of the foam are also poor, making it not an ideal material for sealing battery pack cases.
[0005] CN110862693A has a density of 0.17-0.22g / cm3 by using n-butanol as a porogenic agent. 3A silicone sponge of the present invention is disclosed. Although the CS (50%, 22h, 70°C) of the sponge is less than 3%, it is not suitable as an encapsulant for battery pack cases due to its ultra-low density which sacrifices mechanical properties.
[0006] In addition, the safety of battery packs requires further requirements for the flame retardancy of encapsulants. It has been reported that flame retardancy can be imparted to foamable silicone materials by adding flame retardants. However, V-0 grade flame retardancy is usually achieved by using a large amount of flame retardant, which has a significant impact on the homogeneity of the material, and this method is believed to sacrifice, for example, elasticity and hardness of the foamable material.
[0007] CN106589954A discloses in Example 1 that adding 26% by weight of a flame retardant containing modified aluminum hydroxide and expandable graphite to foamed silicone rubber can achieve flame retardancy of V-0. However, such foamed silicone rubber has poor elasticity and mechanical properties and cannot be used as a sealing material for battery pack cases.
[0008] CN101845224B discloses in Example 4 that adding 22% by weight of flame retardant containing aluminum hydroxide, expandable graphite, ammonium polyphosphate and pentaerythritol to silicone foam can achieve flame retardancy of V-0. However, the elastic performance and mechanical properties of silicone foam are still not satisfactory. Summary of the Invention
[0009] The present disclosure provides a foamable silicone composition that balances two competing reactions, the curing reaction between Si-H and alkenyl groups and the foaming reaction between Si-H and hydroxyl groups, by combining a specific molar ratio of Si-H to alkenyl and a specific molar ratio of Si-H to hydroxyl. If the foaming reaction is too fast, the cured network will be insufficient to support the cell structure, causing cell collapse and affecting product performance. If the foaming reaction is too slow, the cured network will be too strong and the product will not expand easily. However, the foamable silicone composition of the present disclosure overcomes such disadvantages existing in the prior art and achieves at least one of the following goals while obtaining a good cell structure.
[0010] 1) Excellent elasticity under aging conditions, CS (50%, 22h, 110℃), CS D85 (50%, 42d) and C.S. shock (50%, 42d) are both less than 10%, making them highly suitable for sealing battery pack cases with a high degree of sealing. 2) Moderate foam hardness, taking into consideration sealing performance and the mechanical properties of the foam. 3) Without affecting the homogeneity of the foam Excellent flame retardancy (V-0 grade) with only a small amount of flame retardant.
[0011] In this specification, the term "foamable silicone material" refers to a material based on organopolysiloxane that can react in the presence of pore formers, crosslinkers, catalysts and other additives to form a porous structure.Materials with a porous structure include, but are not limited to, foams or sponges.
[0012] In this specification, the "sieved particle size" is measured by a sieved particle size analyzer and is expressed in units of μm.
[0013] A first aspect of the present disclosure is a method for manufacturing a semiconductor device comprising: (A) at least one organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule; (B) at least one organopolysiloxane containing at least two silicon-bonded hydrogen atoms per molecule; (C) at least one pore-forming agent that produces gaseous hydrogen in the presence of component (B); (D) at least one hydrosilylation catalyst, and (E) optionally, at least one inhibitor; and (F) Optionally, at least one reinforcing filler. Contains the molar ratio of SiH groups from component (B) to silicon-bonded alkenyl groups from component (A) is from 5:1 to 15:1, and the molar ratio of SiH groups from component (B) to hydroxy groups from component (C) is from 2:1 to 20:1; A foamable silicone composition is provided.
[0014] Component (A) The organopolysiloxane (A) is usually represented by the following formula: [ka]
[0015] In the formula, R 1 is independently at each occurrence an alkenyl group having 2 to 6 carbon atoms, for example, vinyl, allyl, propenyl, butenyl, hexenyl, hexadienyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, preferably vinyl, allyl and propenyl, more preferably vinyl.
[0016] R 2is independently at each occurrence a substituted or unsubstituted monovalent organic radical having from 1 to 20 carbon atoms, preferably from 1 to 10 carbon atoms, e.g., alkyl, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, etc., aryl or alkaryl, such as phenyl, tolyl, xylyl, mesityl, ethylphenyl, benzyl, naphthyl, etc., and halogenated or organic group-functionalized derivatives of the above groups, such as 3,3,3-trifluoropropyl, o-, p- and m-chlorophenyl, aminopropyl, 3-isocyanatopropyl, cyanoethyl, etc., preferably methyl and phenyl, more preferably methyl.
[0017] m is a positive number, n is 0 or a positive number, and m+n is a value such that the dynamic viscosity of the organopolysiloxane (A) at 25° C. is 1,000 to 100,000 mPa·s, for example, 1,000 to 80,000 mPa·s, or 5,000 to 50,000 mPa·s.
[0018] Organopolysiloxanes (A) of the following formula are particularly preferred: Vi(Me2SiO) m (ViMeSiO) n Vi In the formula, Vi is vinyl, Me is methyl, m is a positive number, n is 0 or a positive number, and m+n is a value such that the kinematic viscosity of the organopolysiloxane at 25° C. is 5,000 to 50,000 mPa·s.
[0019] Component (A) of the present disclosure may be a single alkenyl-containing organopolysiloxane or a mixture of different alkenyl-containing organopolysiloxanes differing in molecular structure (e.g., type and number of substituents), vinyl content, or viscosity. In the case of a mixture of organopolysiloxanes, m and n represent average values, and the viscosity range filled by m+n is for the viscosity of the mixture.
[0020] In order to increase the crosslinking sites and crosslinking density and improve the elastic performance and mechanical properties of the cured foam, component (A) of the present disclosure may also contain a small amount of a low viscosity alkenyl group-containing organopolysiloxane. In one embodiment of the present specification, component (A) includes (A1) a first organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule and having a kinetic viscosity at 25°C of 1,000 to 100,000 mPa·s, for example 5,000 to 50,000 mPa·s, and (A2) a second organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule and having a kinetic viscosity at 25°C of 10 to 1,000 mPa·s, for example 50 to 500 mPa·s. In a more specific embodiment of the present specification, component (A) comprises (A1) a first organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule and having a kinematic viscosity of 10,000 to 30,000 mPa·s at 25° C., and (A2) a second organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule and having a kinematic viscosity of 100 to 300 mPa·s at 25° C. According to any of the above embodiments, organopolysiloxane (A2) is used in an amount of 0.2% by weight to 10% by weight, for example 1% by weight to 5% by weight, based on the total weight of component (A).
[0021] In the present disclosure, component (A) is suitably used in an amount of 35% to 95% by weight, for example 50% to 90% by weight, based on the total weight of the composition.
[0022] Ingredient (B) Component (B) acts as a crosslinking agent in the composition. Component (B) usually has a hydrogen content of 0.01% to 1.7% by weight, preferably 1.2% to 1.7% by weight. The position of the Si-H groups is not particularly limited, and they may be present only as side chain groups, or both as side chain groups and terminal groups.
[0023] The organopolysiloxane (B) may be linear, cyclic, branched or resinous. The linear or cyclic organopolysiloxane (B) is usually2 3SiO 1 / 2 , H.R. 2 SiO 2 / 2 , H.R. 2 2SiO 1 / 2 , and R 2 2SiO 2 / 2 It is composed of units selected from R 2 is as defined above, preferably methyl and phenyl, more preferably methyl. The branched or resinous organopolysiloxane (B) is HSiO 3 / 2 and R 2 SiO 3 / 2 and / or SiO 4 / 2 Me3SiO 1 / 2 , HMeSiO 2 / 2 , HMe2SiO 1 / 2 and Me2SiO 2 / 2 Particularly preferred is a linear or cyclic organopolysiloxane (B) composed of units selected from the following:
[0024] To obtain a foam having high resilience, moderate hardness and good mechanical properties, the molar ratio of SiH groups from component (B) to silicon-bonded alkenyl groups from component (A) of the present disclosure is preferably from 5:1 to 12:1, in particular from 7:1 to 12:1.
[0025] Ingredients (C) Component (C) acts as a pore former in the composition, reacting with the Si-H groups in component (B) to generate gaseous hydrogen, which affects the foaming behavior but does not contribute to crosslinking. Commonly used pore formers are at least one hydroxyl-containing compound, such as organopolysiloxane (C1) containing at least one hydroxyl group, an alkanol and water.
[0026] The organopolysiloxane (C1) is usually represented by the following formula: [ka]
[0027] In the formula, R2 is as defined above, preferably methyl and phenyl, more preferably methyl.
[0028] R 3 represents, independently at each occurrence, a hydroxyl group or R 2 and at least one R 3 is sufficient, and preferably both R 3 is a hydroxyl group.
[0029] p is a positive number, q is 0 or a positive number, and p+q is a value such that the kinematic viscosity of the organopolysiloxane (C1) at 25° C. is 10 to 10,000 mPa·s, for example 50 to 5,000 mPa·s, and particularly 50 to 1,000 mPa·s.
[0030] Organopolysiloxanes (C1) of the following formula are particularly preferred: HO(Me2SiO) p (HOMeSiO) q OH
[0031] In the formula, Me is methyl, p is a positive number, q is 0 or a positive number, and p+q is a value such that the kinematic viscosity of the organopolysiloxane at 25° C. is 50 to 1,000 mPa·s.
[0032] In a preferred embodiment of the present specification, component (C) does not include organopolysiloxane (C1). In this specification, "does not include" means that the content of a certain component in the component is less than 1% by weight, or even less than 0.5% by weight, less than 0.1% by weight, or less than 0.05% by weight.
[0033] The alkanol may be an organic alcohol containing at least one hydroxyl group, but is not limited to alcohols that act as hydrosilylation inhibitors, such as alkynols, and examples thereof include monohydric alcohols having 1 to 12 carbon atoms, such as ethanol, n-propanol and isopropanol, n-butanol, n-hexanol, n-octanol, cyclopentanol, cyclohexanol, cycloheptanol, and polyols having 2 to 12 carbon atoms, such as ethylene glycol, propylene glycol, glycerin, butylene glycol, pentanol glycol, heptane, and the like. In a preferred embodiment of the present specification, component (C) does not contain an alkanol.
[0034] When water is used as a pore-forming agent, it may be introduced in the form of an aqueous emulsion, such as an aqueous silicone emulsion, for example an oil-in-water silicone emulsion or a water-in-oil silicone reverse emulsion, in order to facilitate the dispersion of water in the composition. The aqueous silicone emulsion comprises a polysiloxane oil phase, an aqueous phase and an emulsifier. The emulsifier may be a nonionic emulsifier, an anionic surfactant, a cationic surfactant or a zwitterionic surfactant, preferably a nonionic surfactant. The aqueous silicone emulsion may be obtained by an emulsification process well known to those skilled in the art. The viscosity of the aqueous silicone emulsion is not particularly limited. In a preferred embodiment of the present specification, component (C) is an aqueous emulsion of polysiloxane having a kinetic viscosity at 25°C of 1,000 to 30,000 mPa·s.
[0035] In order to obtain a foam having a moderate density and hardness and having good elasticity and mechanical properties, the molar ratio of SiH groups from component (B) to hydroxyl groups from component (C) of the present disclosure is from 3.5:1 to 12.5:1.
[0036] Ingredients (D) Component (D) can be any of the various hydrosilylation catalysts used in the prior art for addition crosslinking silicone rubbers, and is preferably a platinum-based catalyst, such as chloroplatinic acid, chloroplatinic acid salts, platinum olefin complexes, and platinum alkenylsiloxane complexes. Platinum-based catalysts can be used in amounts that take into account the desired cure rate and economics, and are usually the minimum level required to ensure an effective hydrosilylation reaction. The weight of platinum metal in the foamable silicone composition is usually 0.1 to 500 ppm, for example 1 to 100 ppm.
[0037] Ingredient (E) The foamable silicone composition may further contain an inhibitor (E) to control the pot life and curing rate of the composition. The inhibitor may be any of the various inhibitors used in the art, such as alkynols such as 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, polymethylvinylcyclosiloxanes such as 1,3,5,7-tetravinyltetramethyltetracyclosiloxane, and alkyl maleates. The amount of the inhibitor may be selected according to its chemical structure and the desired curing rate. The weight of the inhibitor in the composition is usually 1 to 50,000 ppm, for example 10 to 10,000 ppm.
[0038] Component (F) In order to obtain a cured foam having good mechanical properties, it is preferable to incorporate a reinforcing filler (F) into the foamable silicone composition. Examples of the reinforcing filler (F) include, but are not limited to, calcium carbonate, silica, fine silica powder, diatomaceous earth, organic montmorillonite, and titanium dioxide. Silica is particularly preferred. Examples of silica include fumed silica, precipitated silica, and mixtures thereof. The specific surface area of the silica, as measured by the BET method, is preferably at least 50 m. 2 / g, preferably 100 to 400m 2 / g range, e.g. 150~350m 2 / g range. Silica can be hydrophilic or hydrophobic.
[0039] The reinforcing filler (F) is suitably used in an amount of 0 to 30% by weight, for example 5 to 25% by weight, preferably 15 to 20% by weight, based on the total weight of the composition.
[0040] Other optional ingredients The foamable silicone composition may further contain an appropriate amount of additives within the range that does not impair the effects of the present invention. Examples of such additives include, but are not limited to, compression set auxiliary (G), halogen-free flame retardant (H), diluent (I), thixotropic agent (J), and pigment (K).
[0041] The example of the compression set auxiliary (G) to be mentioned is an organic sulfur compound, for example, mercaptan such as alkylthiol, arylthiol, mercapto heterocyclic compound such as mercapto imidazole and mercapto benzimidazole, for example, silane with sulfur-containing functional group such as mercapto alkyl alkyl alkoxy silane, bis (trialkoxy silyl alkyl) mono, di or polysulfane, thiocyanato alkyl trialkoxy silane, for example, thiofunctional siloxane such as polydimethylsiloxane-co-mercapto alkyl compound.Preferably, 3-mercaptopropyl trimethoxy silane, 3-mercaptopropyl triethoxy silane, polydimethylsiloxane-co-mercapto alkyl compound.
[0042] The organosulfur compound of the present disclosure may be used alone, or may be applied to, reacted with, or blended with a filler. In one embodiment of the present disclosure, fumed silica coated, reacted with, or blended with 3-mercaptopropyltrimethoxysilane or 3-mercaptopropyltriethoxysilane is used as a compression set aid. The organosulfur compound of the present disclosure is preferably used in an amount of less than 2 wt%, for example less than 1 wt%, based on the total weight of the composition. In one embodiment of the present disclosure, the organosulfur compound accounts for 0.2 wt% to 0.8 wt% of the total weight of the composition.
[0043] Examples of the halogen-free flame retardant (H) include, but are not limited to, aluminum-magnesium-based flame retardants such as aluminum hydroxide and magnesium hydroxide, phosphorus-based flame retardants such as ammonium polyphosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, magnesium phosphate, red phosphorus, tributyl phosphate, tris(2-ethylhexyl) phosphate, cresyl diphenyl phosphate, tricresyl phosphate, triphenyl phosphate, and (2-ethylhexyl)-diphenyl phosphate, nitrogen-based flame retardants such as melamine and its derivatives, triazine and its derivatives, carbon-based flame retardants such as carbon black, expandable graphite, expandable graphite, carbon nanotubes, fullerenes, and graphene, silicone-based flame retardants such as polydimethylsiloxane, polysilsesquioxane, and silicone resins, and boron-based flame retardants such as zinc borate. Carbon-based flame retardants are preferred. In one embodiment of the present specification, the halogen-free flame retardant is expandable graphite and may not contain other halogen-free flame retardants.
[0044] Component (H) is used in at least the minimum level necessary to ensure effective flame retardancy. Usually, the higher the amount of component (H), the better the flame retardancy of the silicone foam. However, in order not to significantly affect the homogeneity of the silicone foam, component (H) is preferably used in an amount of less than 20 wt%, for example less than 15 wt%, more preferably less than 10 wt%, based on the total weight of the composition. In one embodiment of the present specification, the halogen-free flame retardant is a carbon-based flame retardant that accounts for 5 wt% to 15 wt% of the total weight of the composition. In a more specific embodiment of the present specification, the halogen-free flame retardant is expandable graphite that accounts for 5 wt% to 10 wt%, for example 5 wt% to 8 wt%, of the total weight of the composition. The halogen-free flame retardant preferably has a sieved particle size of 80 to 200 μm, for example 80 to 150 μm, 80 to 120 μm. Surprisingly, the halogen-free flame retardant having a particle size within the above range can significantly reduce the amount of flame retardant added.
[0045] Examples of the diluent (I) that should be mentioned include dimethyl silicone oil having a dynamic viscosity of 10 to 5,000 mPa·s at 25° C., MDT silicone oil having a dynamic viscosity of 15 to 300 mPa·s at 25° C., and 10 to 100 mm 2 Mineral oils having a kinematic viscosity of 1000 / s can be used. Usually, the addition of a diluent reduces the viscosity of the composition and can change its rheological properties. Nevertheless, in consideration of potential bleeding problems, the foamable silicone composition of the present disclosure can be free of a diluent.
[0046] Thixotropic agents (J) which should be mentioned include, for example, polyethers, such as polyethylene oxide, polypropylene oxide, copolymers of ethylene oxide and propylene oxide, and polyether-modified silicones, such as DC 193 supplied by Dow Corning, TEGOPREN 3022, TEGOPREN 3070, TEGOPREN 5878, TEGOPREN 5847 supplied by Evonik Industries.
[0047] The foamable silicone composition of the present disclosure can be stored as two separate packages, where components (B) and (C) are not stored in the same package, and components (A), (B) and (D) are not stored in the same package.
[0048] The composition of the present disclosure, or each of the separate packages described above, preferably has a viscosity of 50,000 to 500,000 mPa·s, for example, a viscosity of 100,000 to 300,000 mPa·s. Typically, the higher the viscosity of the composition, the lower the density of the resulting foam. Compositions of the present disclosure having a high viscosity cure to form foams of medium density, taking into account both foam density and mechanical properties.
[0049] A second aspect of the present disclosure provides a foam formed from the foamable silicone composition of the first aspect of the present disclosure.
[0050] This is obtained by crosslinking or curing the composition according to the first aspect of the present disclosure, or by mixing the separate packages mentioned above, followed by crosslinking or curing.
[0051] Crosslinking or curing is usually carried out at a temperature of 15 to 180°C for 10 minutes to 72 hours. Lower curing temperatures and shorter curing times are preferred. Considering that the curing reaction and the foaming reaction occur simultaneously and are both very sensitive to temperature, it is preferable to cure at a temperature of 70 to 150°C for 15 to 60 minutes in order to balance these two reactions and obtain a good cell structure.
[0052] The foam of the present disclosure has a density of 0.4 to 0.6 g / cm 3 and a closed cell percentage of more than 90%. The foam density is measured according to standard GB / T 6343-2009 Cellular plastics and rubbers-Determination of apparent density. The closed cell percentage is measured according to standard GB / T 10799 2008 Rigid cellular plastics-Determination of the volume percentage of open cells and of closed cells.
[0053] A third aspect of the present disclosure provides a use of the foamable silicone composition of the first aspect of the present disclosure for sealing a battery pack case, particularly a battery pack case of an electric vehicle.
[0054] This use particularly advantageously includes dispensing via an automatic dispenser, curing the composition according to the first embodiment of the present disclosure, and then compressing to achieve sealing between the bottom plate and the top cover of the battery case. If the hardness of the foam cured from the foamable silicone composition is too high, it becomes difficult to compress, and the top cover of the case is easily deformed, making processing and sealing difficult.
[0055] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be further described by the following examples, but is not limited in scope. In the following examples, the experimental methods for which conditions are not specified are selected according to conventional methods and conditions or product specifications.
[0056] Compression set under high temperature conditions This is done according to the standard GB / T 6669-2008 Flexible cellular polymeric materials-Determination of compression set, section 7, method C. The result is expressed as CS(%) (compression amount / %, compression time / h, compression temperature / ℃) and is calculated according to the following formula: CS=(d0-d r ) / d0×100% where CS is the compression set value expressed as a percentage (%). d0 is the initial thickness of the sample (unit: mm). d r is the final thickness of the sample (unit: mm).
[0057] The value of CS varies depending on the test conditions. Usually, the smaller the compression amount, the shorter the compression time, and the lower the compression temperature, the smaller the CS value. CS(%) (50%, 22h, 70°C) is generally used to determine the compression set of soft foam polymer materials. However, the CS value measured at a temperature of 100°C may be obviously or significantly larger than the CS value measured at 70°C, so even if the CS value measured under such test conditions is low, it cannot be said that the corresponding foam material is suitable for sealing a battery pack case with high sealing degree. Since heat is easily accumulated inside the battery, a foam material with a low CS value at high temperatures, for example, 110°C, is desired for sealing the battery pack case, so in the present invention, CS(%) (50%, 22h, 110°C) is used to evaluate the compression set of the foam under high temperature conditions.
[0058] Compression set under high temperature and humidity conditions The conditions of the equipment, measuring instruments and samples are in accordance with standard GB / T 6669-2008, and the test process is as follows: the samples to be tested are adjusted at a temperature of (23±2)℃ and a relative humidity of 50%±5% for 16 hours, then placed between the two plates of the equipment and compressed to a thickness of 50% of the initial thickness measured according to standard GB / T 6342, and within 15 minutes, these samples are placed in an oven at a constant temperature of 85℃ and a constant relative humidity of 85% for 1000 hours without changing their shape, during which the samples are taken out of the oven on the 7th, 14th, 28th and 42nd days, and left at a temperature of (23±2)℃ and a relative humidity of 50%±5% for 2 hours, after which the thickness is measured, and the CS value is calculated according to the above formula, and the results are expressed as CS D85 Expressed as (%) (amount compressed / %, time compressed / day).
[0059] Compression set under thermal shock conditions The conditions of the equipment, measuring instruments and samples are in accordance with standard GB / T 6669-2008, and the test process is as follows: the samples to be tested are conditioned at a temperature of (23±2)℃ and a relative humidity of 50%±5% for 16 hours, then placed between the two plates of the equipment and compressed to a thickness of 50% of the initial thickness measured in accordance with standard GB / T 6342, and within 15 minutes, these samples are placed in a thermal shock box that performs 1000 cycles of -40℃ (30 minutes) to 85℃ (30 minutes) without changing the shape, and on the 7th, 14th, 28th and 42nd days during this period, the samples are taken out of the oven and left at a temperature of (23±2)℃ and a relative humidity of 50%±5% for 2 hours, after which the thickness is measured, and the CS value is calculated according to the above formula, and the results are expressed as CS shock Expressed as (%) (amount compressed / %, time compressed / day).
[0060] Hardness Measurement For the measurement, an LX-C microporous material hardness tester is used. Sample size: thickness 10±0.5mm, width ≥30mm, length ≥60mm.
[0061] Measurement of tensile strength and elongation at break This is done in accordance with the standard GB / T 6344-2008 Flexible cellular polymeric materials-Determination of tensile strength and elongation at break.
[0062] Flame Retardancy Test This is done in accordance with the UL94V standard using samples with dimensions of 120mm length x 13mm width x 2mm thickness. The results are assessed according to the following grades: V-0: Maximum flame duration of less than 10 seconds, no dripping of combustion material (excellent flame retardancy) V-1: Maximum afterflame time less than 30 seconds, no dripping of combustion material (good flame retardancy) V-2: Maximum flame duration of less than 30 seconds, with dripping of combustion material (normal flame retardancy) NC: Not classified (poor flame retardancy)
[0063] Details of the raw materials used in the examples and comparative examples are as follows. A1: Dimethylvinylsiloxy-terminated polydimethylsiloxane with a kinematic viscosity of approximately 20,000 mPa·s at 25°C, supplied by Wacker Chemicals. A2: Dimethylvinylsiloxy-terminated polydimethylsiloxane with a kinematic viscosity of approximately 190 mPa·s at 20 °C according to DIN 53019, supplied by Wacker Chemicals. B: Hydrogen-containing polydimethylsiloxane having a hydrogen content of 1.63% by weight; Supplied by Wacker Chemicals. C1: Water-based emulsion of polydimethylsiloxane with a kinematic viscosity of 5,000–10,000 mPa·s at 25°C and a hydroxyl content of 59.9% by weight, supplied by Wacker Chemicals. C2: Dimethylhydroxylsiloxy terminated polydimethylsiloxane with a hydroxyl content of 1.2 wt%, supplied by Wacker Chemicals. D: Platinum-based catalyst, WACKER (registered trademark) CATALYST EP, Supplied by Wacker Chemicals. E: Inhibitor, WACKER® INHIBITOR PT 88; Supplied by Wacker Chemicals. F: BET surface area is 150-350m 2 / g fumed silica, Supplied by Wacker Chemicals.
[0064] G: Compression set aid, prepared by the following steps: 1) 10 g of water was mixed with 100 g of component F with stirring at room temperature and atmospheric pressure, followed by the addition of 12.24 g of 3-mercaptopropyltrimethoxysilane (both as fine powders) to the mixture, which was then annealed at 80° C. for 1 hour and the reaction by-products were removed under reduced pressure to yield 106.1 g of a white powder.
[0065] 2) 43.3 parts by weight of component A1 was mixed with 20 parts by weight of component F in a kneader and processed to obtain a homogenous composition. Then, 10 parts by weight of the white powder obtained in the above step was added to this composition, and then homogenized at 120°C for another 0.5 hours. Finally, 26.7 parts by weight of component A1 was blended to obtain 93.3 g of compression set aid.
[0066] H1: Expandable graphite with a sieved particle size of 100 μm. H2: Expandable graphite with a sieved particle size of 75 μm.
[0067] Examples 1 to 8 and Comparative Examples 1 to 2 The components in Component A and Component B were thoroughly mixed according to the formulation in Table 1. Component A and Component B were then mixed in a 1:1 ratio and cured at 80°C for 0.5 hours to obtain a silicone foam.
[0068] Table 2 shows the test results of density, compression set and hardness for the foams obtained in each Example and Comparative Example. From Table 2, it can be seen that the foams obtained in Examples 1 to 8 have CS (50%, 22h, 110°C) of 10% or less, exhibit excellent elasticity, and have moderate hardness, which are very useful for sealing the battery pack case. Since the Si-H / OH molar ratio of the foamable composition of Comparative Example 1 is too low, the CS of the foam obtained increases significantly and does not provide a sealing effect. Since the Si-H / Si-Vi molar ratio of the foamable composition of Comparative Example 2 is too high, the CS of the foam obtained also increases obviously, the foam hardness increases, and there is a high possibility that this will cause a defective sealing of the battery pack case.
[0069] Table 3 shows that the compression set of the foam obtained in Example 4 under high temperature and high humidity or thermal shock is 10% or less, indicating good aging resistance and suitable for sealing battery pack cases with high sealing degree. Table 4 shows that the foam obtained in Example 1 has excellent mechanical properties, and the incorporation of a certain amount of expandable graphite does not obviously deteriorate the mechanical properties of the foam.
[0070] Table 5 shows that the foamable composition of Example 4 containing an amount of expandable graphite H1 achieves excellent flame retardancy of V-0 grade, but it should be noted that such flame retardancy is not achieved at the expense of significantly increased foam CS and hardness. The foamable compositions of Examples 5-6 containing an amount of expandable graphite H2 have poor flame retardancy of NC grade.
[0071] [Table 1]
[0072] [Table 2]
[0073] [Table 3]
[0074] [Table 4]
[0075] [Table 5]
Claims
1. (A) 35% to 95% by weight of at least one organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule; (B) at least one organopolysiloxane containing at least two silicon-bonded hydrogen atoms per molecule; (C) at least one pore former that produces gaseous hydrogen in the presence of component (B); and (D) at least one hydrosilylation catalyst Contains Component (A) contains an organopolysiloxane (A) represented by the following formula (1): the molar ratio of SiH groups from component (B) to silicon-bonded alkenyl groups from component (A) is from 5:1 to 15:1 and the molar ratio of SiH groups from component (B) to hydroxy groups from component (C) is from 2:1 to 20:1; The content of the organopolysiloxane represented by the following formula (2) in component (C) is less than 1% by weight: The content of alkanol in component (C) is less than 1% by weight. A foamable silicone composition. 【Chemistry 1】 [In formula (1), R 1 is, independently at each occurrence, an alkenyl group having 2 to 6 carbon atoms; R 2 is, independently at each occurrence, a substituted or unsubstituted monovalent organic group having 1 to 20 carbon atoms; m is a positive number; n is 0 or a positive number; and m+n is a value such that the kinematic viscosity of organopolysiloxane (A) at 25° C. is 100 to 100,000 mPa·s.] HO(Me 2 SiO) p t0.834597 q OH(2) [In formula (2), Me is methyl, p is a positive number, q is 0 or a positive number, and p+q is a value such that the kinematic viscosity of the organopolysiloxane at 25° C. is 50 to 1,000 mPa·s.]
2. 2. The composition of claim 1, wherein the molar ratio of SiH groups from component (B) to hydroxy groups from component (C) is from 3.5:1 to 12.5:
1.
3. 3. The composition of claim 1 or 2, characterized in that the molar ratio of SiH groups from component (B) to silicon-bonded alkenyl groups from component (A) is from 7:1 to 12:
1.
4. 4. The composition according to claim 1, wherein component (B) has a hydrogen content of 1.2% to 1.7% by weight.
5. Component (A) is (A1) a first organopolysiloxane containing at least two silicon-bonded alkenyl groups per molecule and having a kinematic viscosity at 25° C. of 1,000 to 100,000 mPa·s; and (A2) a second organopolysiloxane which contains at least two silicon-bonded alkenyl groups per molecule and has a kinetic viscosity at 25°C of 10 to 1,000 mPa·s; The composition according to any one of claims 1 to 4, characterized in that it contains
6. The composition according to any one of claims 1 to 5, characterized in that the pore-forming agent (C) comprises water.
7. The composition, (E) at least one inhibitor The composition according to any one of claims 1 to 6, further comprising:
8. The composition, (F) at least one reinforcing filler The composition according to any one of claims 1 to 7, further comprising:
9. 9. The composition of claim 8, wherein the reinforcing filler (F) comprises fumed silica.
10. The composition, (G) Organic sulfur compound The composition according to any one of claims 1 to 9, further comprising:
11. The composition according to any one of claims 1 to 10, characterized in that the composition has a kinematic viscosity at 25°C of 50,000 to 500,000 mPa·s.
12. The composition, (H) Halogen-free flame retardants The composition according to any one of claims 1 to 11, further comprising:
13. The composition according to claim 12, characterized in that the halogen-free flame retardant has a sieved particle size of 80 to 200 μm.
14. 14. The composition according to claim 12 or 13, characterized in that the halogen-free flame retardant is used in an amount of 5% to 15% by weight relative to the total weight of the composition.
15. The composition according to any one of claims 12 to 14, characterized in that the halogen-free flame retardant is a carbon-based flame retardant.
16. A foam formed by crosslinking from the composition according to any one of claims 1 to 15.
17. Use of the composition according to any one of claims 1 to 15 for sealing a battery pack case.
Citation Information
Patent Citations
Flame-retardant foamed silicone rubber and preparation method thereof
CN109161205A
Double-component liquid silicone rubber for foam with ultralow compression set rate
CN110862693A
Organopolysiloxane composition convertible to heat-resistant foam
JP1986183326A
Fire-resistant silicone foam composition
JP1987043435A
Low-viscosity silicone foam composition
JP1990086633A